UNREGISTERED MARRIAGE IN ISLAMIC LAW PERSPECTIVE A CRITICAL STUDY OF ISLAMIC LAW COMPILATION - Maloko, Muhammad Tahir (Islamic University of Indonesia, 2015)
This article below constitutes authorâs dissertation that discusses the âunregistered marriage ( nikah sirri ) in perspective of Islamic law a critical study of Islamic Law Compilationâ. The problem statement of this, namely: how is nikah sirri in the perspective of Islamic law, what factors denote the background of nikah sirri, and how is the impact for those who do marriage nikah sirri? Unregistered marriage or nikah sirri according to Islamic law is valid if it meets the requirements harmonious and marriage. As for the cause, among others: economic factors, social status and moral crisis. Meanwhile the impact that would arise from a marriage that is not recorded are nominally: the marriage is considered invalid, even though the marriage was performed according to the religion and beliefs, but in the eyes of the state of marriage is invalid if it has not been noted by KUA or Civil Registry Office, Children born from such marriage only have a civil relationship with the mother and the motherâs family, while a civil relationship with his father was not there. It means that the child can not claim the rights of the father. By being born in a marriage that is not recorded, the birth of a child becomes legally registered also in violation of the rights of children. Childrenâs status as children outside of marriage. Further result of marriage is not recorded, both wife and children were born of the marriage is not entitled to demand a living or inherited from his father. Keywords : KHI, Islamic Law, Unregistered Marriage, Legal Status.